A study on the implementation on the conservation and preservation of heritage site as provided in the National Heritage Act 2005: a study on Malacca heritage site / Amirah Soeraya Zakaria…[et al.] - Zakaria, Amirah Soeraya; Zulkanain, Nadiah An-Najihah; Raja Abdul Aziz, Raja Arith Sofia (Faculty of Law, 2009)
This project paper is concerning the importance and purpose of conservation and preservation of National Heritage in Malaysia. The National Heritage Act 2005 being a newly gazetted act and provision, in conserving and preserving heritage sites thus after a few years being gazetted, it is important to determine the extent of its implementation because this will show how effective it is. This project paper will touch on the laws and its components in conserving heritage which emphasised on Malacca as the case study. Furthermore the application of Malacca Enactment 1988 will be mentioned and other relevant provisions and measures in conserving will be included. Therefore a comparative study will be done in determining the strength and weaknesses of these laws will also be pointed out. In addition, this research paper will also include a case study in order to determine the practicability and the effectiveness of these laws. The obstacles and challenges of the Act towards protecting and conserving the heritage sites will be identified especially in Malacca and also ways to overcome the situation. In the end of this project paper, which is chapter 5 recommendations will be proposed based on the findings of the research with the hope to increase effectiveness of the laws on conserving and preserving the heritage sites.